Hair cortisol sampling as a measure of physiological stress in youth with acute musculoskeletal pain - Wendy Gaultney; Jacqueline R. O'Brien; Jessica Heierle; Eleanor A.J. Battison; Anna Wilson; Cynthia Rovnaghi; Kanwaljeet J.S. Anand; Amy Holley (Comprehensive Psychoneuroendocrinology)
Stress physiology contributes to health outcomes. Hair cortisol concentration (HCC) is an objective measure of cumulative cortisol secretion associated with health, including pain. The aim of the current study was to describe associations between pre-injury stress physiology (as measured by HCC), acute pain characteristics and relevant demographic factors (i.e., BMI, age, sex, days since injury) in youth with an acute musculoskeletal (MSK) injury. Participants were 58 youth aged 11 to 17 with acute MSK pain. Participants completed self-report measures assessing pain intensity, pain catastrophizing, and pain interference. Hair was collected within 1 month after injury using hair cortisol collection procedures adapted from published research protocols. Correlations examining associations among HCC values and clinical/demographic factors revealed that higher HCC was associated with lower body mass index (BMI) and male sex. HCC was not associated with pain variables or age. Additional research is needed to clarify the relation between HCC and psychosocial variables to aid researchers in studying the role of pre-injury stress in acute MSK injury and pain recovery in youth.